Pengaruh Reward dan Punishment Terhadap Kinerja Karyawan di KSU Postra - Edwin Lucky Gunawan Setiadi; Kusuma Agdhi Rahwana; Nita Fauziah Oktaviani (J-CEKI : Jurnal Cendekia Ilmiah, 2023)
This study aims to determine and analyze the effect of reward and punishment on employee performance at KSU Postra simultaniosely and partial. The method used in this research is causality with a quantitative approach. With a research sample of 49 employees in the marketing department at KSU Postra. The data used is using primary data. The analytical tool used in this study is multiple regression using SPSS 26.0. The results showed. Together Reward and Punishment have a significant influence on Employee Performance at KSU Postra Employees. Partially Reward has a significant influence on Employee Performance at KSU Postra. Partially, punishment has a significant effect on employee performance at KSU Postra